Residual Stresses in Ultrafine-Grained Laminated Metal Composites Analyzed by X-ray Diffraction and the Hole-Drilling Method - Kümmel, Frank; Magnier, Arnauld; Wu, Tao; Niendorf, Thomas; Höppel, Heinz Werner (Advanced Engineering Materials, 2022)
Accumulative roll bonding is an advanced manufacturing process, which is capable of simultaneously refining the grain size into the nanometer regime and bonding different metallic sheet materials. Herein, homogenous aluminum/aluminum as well as heterogeneous aluminum/steel laminated metal composite (LMCs) are fabricated. The residual stresses are experimentally determined by X-ray diffraction and the hole-drilling method. Generally, a complex residual stress profile is found in all LMCs. The level of residual stress strongly depends on the bonded materials. Compressive residual stresses are induced in all sheets in the near surface area. These stresses range from -5 MPa in aluminum to -240 MPa in steel. In the homogenous aluminum/aluminum LMCs, compressive stresses up to -26 MPa in the softer layers and tensile stresses up to 30 MPa in the stronger layers are built up. This is different to heterogeneous aluminum/steel LMCs, where tensile stresses up to 40 MPa in the softer aluminum layers and compressive stresses up to -72 MPa in the inner harder steel layers are present. Based on the results obtained it is possible to directly design the material combination or stacking architecture of ultrafine-grained LMCs to tailor the residual stress profile.
CRIS-Team WoS Importer:2022-05-27